Caracterização ambiental, florística e fitossociológica de uma Unidade de Conservação. Caso de estudo: Estação Ecológica de São Carlos, Brotas, SP - Feliciano, Ana Licia Patriota (Universidade Federal de São Carlos, 1999)
The present work was carried oput to develop na environmental characterization and diagnosis of the Ecologic Station of São Carlos and to estabilish a basic for the knowledge of the ecology of the arboreal species present in this fragment of semideciduous seasonal forest to support the planning and management of this conservation unit, and also to allow the maintenance and conservation of theirs existing natural resources. The Ecological Station of São Carlos, located between the municipalities of São Carlos and Brotas, São Paulo State, Brazil, with an area of 75,26 ha, it is a forest fragment constituted of a deciduous seasonal forest and is limitd by sugar-cane crops and the Santana dam. As one of the Conservation Units of the São Paulo State without scientific information, it deserves a study about its characterization and boundaries together whith the knowledge of its floristics and phytosociology, to elaborate its zoning, using the Geographic Information System (GIS/IDRISI). The use of GIS was important to the environmental characterization of the area and its boundaries, to provide information on its hydrography, altimetry, slopes, soil, municipalies boundaries, road system, use and soil cover, which resulted in the thematic maps (altimetric, hydrographic, etc) and the environmental zoning. To evaluate the consequences of the fragmentation process of the study area, in view of the unknown biologic diversity, specially vegetation, the floristic and phytosociologic surveys were carried out as a starting point for various works to be further developed in the area. The study of the floristics and phytosociology of the arboreal stratum was carried out by means of four transects, in which blocks of 10 x 10 m were established. In addition, the level of infestation by vines on the trees and dead trees was evaluated. The survey allowed the identification of 97 species distributed among 37 families, from which Fabaceae and Meliaceae contributed with the highest number of species. Fifteen individuais were not identified at species level. From this total, four were identified at family level, ten at genus level and one is unknown. The diversity index obtained for the species in the studied area was of 3.55 nats/species. Three of the species found, Zanthoxylum riedelianum Engl., Trichilia hirta L., and Astronium fraxinifolium Schott are included among the endangered species, in the vulnerable category. With the results of arboreal flora found in the survey. The richness of families and species was found to be quite similar when compared to studies of other fragments of the State of São Paulo. The need of elaborating and accomplishing a specific management plan for the area is assential for maintenance and conservation of the associeated genetic resources of this conservation unit, due to the agricultural use of its boundaries.
Keywords: Ecologia florestal; Florística; Análise ambiental; Unidade de conservação; Zoneamento; Sistema de Informação Geográfica (SIG); CIENCIAS BIOLOGICAS